3D concrete printing of permanent formwork for concrete column construction. (August 2021) - Zhu, Binrong; Nematollahi, Behzad; Pan, Jinlong; Zhang, Yang; Zhou, Zhenxin; Zhang, Yamei
Abstract: This study investigated 3D concrete printing of permanent formwork for concrete column construction. The effect of different hydroxypropyl methyl cellulose (HPMC) contents (0, 0.0003 and 0.0006 by mass of binder) and the water-to-binder (W/B) ratios (0.27, 0.29 and 0.31) on the rheological properties, structural build-up and mechanical performance were studied using several mixtures for manufacture of the permanent formworks. The results showed that the mixture with the HPMC = 0.0006 and the W/B = 0.27 showed the maximum static yield stress, largest thixotropy and maximum green strength, and thereby selected as the optimum mixture. The plastic failure of the optimum mixture was also predicted using a thixotropy model and was compared with the experimental results. Subsequently, three concrete columns with different longitudinal steel reinforcement ratios (0.0%, 1.9% and 2.5%) were constructed using the printed concrete as the permanent formwork and tested in compression. Good bonding was observed at the interface of the cast-in-place concrete and the printed concrete permanent formwork. In addition, it was observed that the initial stiffness, the maximum bearing capacity and the corresponding longitudinal displacement of the concrete columns increased, as the longitudinal reinforcement ratio increased. The counterpart concrete columns using the conventional formworks were also constructed and tested for comparison. In comparison, the concrete columns made using the printed concrete as the permanent formwork obtained a higher stiffness and bearing capacity than the counterpart conventional concrete columns. The reasons for the differences are explained.